The negotiator [large type] : a memoir - Mitchell, George J. (George John), 1933- (Thorndike Press, A part of Gale, Cengage Learning, 2015)
Growing up in a working class Maine family that made education a priority, George Mitchell embraced every opportunity. In a classic story of the American Dream, he went on to become the ranking Democrat in the U.S. Senate and the architect of peace in Northern Ireland. With frankness and wit, Senator Mitchell looks back on law and politics, in the last half century, and what he's learned about the art of negotiation during every stage of his life.